1996
DOI: 10.1002/hep.510240525
|View full text |Cite
|
Sign up to set email alerts
|

Fibrolamellar Carcinoma of the Liver: Composition of the Extracellular Matrix and Expression of Cell–Matrix and Cell–Cell Adhesion Molecules

Abstract: sinophilic, neoplastic, epithelial cells resembling hepatoWe have analyzed the composition of the tumor stroma cytes. 1,2,[4][5][6][7][8] The prognosis of FLC is usually favorable. [1][2][3][8][9][10] In and the expression of cell-matrix and cell-cell adhesion most cases, tumors are resectable at diagnosis, and prolonged molecules in 11 cases of fibrolamellar carcinoma of the survivals are obtained after surgical resection or liver transliver (FLC), in comparison with 34 cases of hepatocelluplantation. lar car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 37 publications
4
20
0
Order By: Relevance
“…To investigate the loss of substrate anchorage, we analyzed the profile of expression of integrins, which are the major receptors mediating the ECM attachment. We concentrated on the integrin subunits known to be expressed by hepatocytes under physiological and pathological conditions (Stamatoglou and Hughes, 1994;Scoazec et al, 1996). In agreement with published data (Bhowmick et al, 2001) the RTqPCR analysis of the principal hepatic integrin ␤ mRNA, ␤1, showed a slight increase in response to TGF-␤ (Figure 4).…”
Section: Tgf-␤ Alters the Pattern Of Expression Of Integrinssupporting
confidence: 71%
See 1 more Smart Citation
“…To investigate the loss of substrate anchorage, we analyzed the profile of expression of integrins, which are the major receptors mediating the ECM attachment. We concentrated on the integrin subunits known to be expressed by hepatocytes under physiological and pathological conditions (Stamatoglou and Hughes, 1994;Scoazec et al, 1996). In agreement with published data (Bhowmick et al, 2001) the RTqPCR analysis of the principal hepatic integrin ␤ mRNA, ␤1, showed a slight increase in response to TGF-␤ (Figure 4).…”
Section: Tgf-␤ Alters the Pattern Of Expression Of Integrinssupporting
confidence: 71%
“…The pattern becomes somewhat more complex in hepatocellular carcinoma where, in addition to an increase in the ␣5 subunit, the ␣3 and ␣6 chains are also abundantly expressed (Scoazec et al, 1996). We found that TGF-␤ induced high level expression of ␣5 and ␣6 in the mhAT3F cells, whereas the ␣3 expression remained constantly low (data not shown).…”
Section: Discussionmentioning
confidence: 65%
“…However, noninvasive HCC cells express MT1-MMP but do not migrate on Ln-5, even in the presence of added exogenous MMP-2. These contradictory results might be explained by the fact that nonmigratory cells hardly express ␣3␤1 integrin, which is also absent in normal adult hepatocytes; whereas it is highly expressed in hepatocytes that are migrating from the endoderm germ layer to the mesenchyme of the septum transversum during embryogenesis (Lora et al, 1998;Nejjari et al, 1999;Scoazec et al, 1996). We found that ␣3␤1 was expressed in HCC tissue, suggesting a role for this integrin in migration on ECM components such as Ln-5 and in metastasis formations.…”
Section: Giannelli Et Almentioning
confidence: 73%
“…In squamous carcinomas of the mouth and larynx a general increase of tenascin-C staining was found to correlate with invasiveness and malignancy [144][145][146][147]. Tumours of the lung [148][149][150], liver [151], kidney, and bladder [152,153] all showed increased tenascin-C staining, most prominent in the stroma at the invasion borders. The number of reports is not yet large enough to make any general statements, although some reports raise the hope that tenascin-C staining could have diagnostic value.…”
Section: Association Of Tenascin-c With Cancer: Antibodies As Diagnosmentioning
confidence: 99%